Targeting Mitochondrial-Derived Reactive Oxygen Species in T Cell-Mediated Autoimmune Diseases - Chávez, Miranda D.; Tse, Hubert M. (Frontiers in Immunology, 2021)
Mitochondrial dysfunction resulting in oxidative stress could be associated with tissue and cell damage common in many T cell-mediated autoimmune diseases. Autoreactive CD4 T cell effector subsets (Th1,Th17) driving these diseases require increased glycolytic metabolism to upregulate key transcription factors (TF) like T-bet and RORγt that drive differentiation and proinflammatory responses. However, research in immunometabolism has demonstrated that mitochondrial-derived reactive oxygen species (ROS) act as signaling molecules contributing to T cell fate and function. Eliminating autoreactive T cells by targeting glycolysis or ROS production is a potential strategy to inhibit autoreactive T cell activation without compromising systemic immune function. Additionally, increasing self-tolerance by promoting functional immunosuppressive CD4 T regulatory (Treg) cells is another alternative therapeutic for autoimmune disease. Tregs require increased ROS and oxidative phosphorylation (OxPhos) for Foxp3 TF expression, differentiation, and anti-inflammatory IL-10 cytokine synthesis. Decreasing glycolytic activity or increasing glutathione and superoxide dismutase antioxidant activity can also be beneficial in inhibiting cytotoxic CD8 T cell effector responses. Current treatment options for T cell-mediated autoimmune diseases such as Type 1 diabetes (T1D), multiple sclerosis (MS), rheumatoid arthritis (RA), and systemic lupus erythematosus (SLE) include global immunosuppression, antibodies to deplete immune cells, and anti-cytokine therapy. While effective in diminishing autoreactive T cells, they can also compromise other immune responses resulting in increased susceptibility to other diseases and complications. The impact of mitochondrial-derived ROS and immunometabolism reprogramming in autoreactive T cell differentiation could be a potential target for T cell-mediated autoimmune diseases. Exploiting these pathways may delay autoimmune responses in T1D.